Coupling effect of delamination cracks and vertical cracks on local phase transition of ceramic topcoat in thermal barrier coatings. Issue 8 (15th April 2023) - Dong, Hui; Xu, Long; Zhou, Pan-Hu; Yang, Guan-Jun; Wang, Li-Shuang; Yao, Jian-Tao
Abstract: The phase transition of atmospheric plasma-sprayed yttria-stabilized zirconia (APS YSZ) coating over delamination cracks in thermal barrier coatings (TBCs) was addressed by gradient thermal cycling test at 1150 °C to illustrate the coupling effect of delamination cracks and vertical cracks in TBCs on the phase transition. Phase structure of 15 dot-matrix micro-regions across YSZ thickness was examined by Raman spectroscopy. Three two-dimensional models were built to elaborate the local temperature evolution in the YSZ coating. The phase transition of YSZ had a markedly time-space characteristic with application duration, depending on the temperature increment. The phase-transition quantity decreased radioactively from the delamination crack center to its tip and gradually decreased from the YSZ free surface to the YSZ/bond coat interface. Compared with YSZ coating only containing delamination cracks or only vertical cracks, the temperature in the YSZ coating was significantly elevated by the combination of vertical cracks and delamination cracks. The increment was in 75 °C–295 °C when the delamination crack propagated from 0.5 mm to 4.0 mm. Consequently, due to the coupling effect of delamination cracks and vertical cracks, serious sintering and phase transition of the YSZ coating would occur once the delamination crack length was beyond 0.5 mm.